Essays on Labour Mobility in Western Europe - Belessiotis-Kalliris, Anastasios (My University, 1981)
Labour migration in Western Europe in the post-World War II period provides substantial evidence of mobility of human resources. Unlike internal migration, which is not inhibited by institutional obstacles, and in contrast to settlement-oriented international migration, intra-European migration has been controlled by the authorities of the labour importing countries and has been of temporary nature, utilized to moderate labour market imbalances. The purpose of this dissertation is to contribute two essays to the literature on intra-European migration. The first essay concerns the impact of labour mobility on labour market adjustments and, more specifically, on wage determination and on the state of excess demand for labour. A model is developed on the hypotheses that, first, wage adjustments, responding to the state of excess demand for labour, are simultaneously determined with quantity adjustments which take the form of migration-induced shifts in the labour supply curve; and, secondly, that wage adjustments are responsive to the characteristics of the structure of the labour market represented by the vacancies-unemployment relationship. Furthermore, it is recognized that mobile labour in Western Europe may be distinguished by EEC and non-EEC citizenship. This distinction is implemented by assuming that mobility of EEC citizens can be explained by the human capital theory of migration, while mobility of non-EEC citizens is determined by a government behavioural function. The model is estimated using West German data. The results confirm that wage adjustments and the state of excess demand for labour are influenced by labour mobility and that the slope of the short-run Phillips curve becomes flatter when the labour market is open. The second essay of the dissertation provides a framework to analyse the determinants of diversification of the foreign labour stock in Western European countries distinguished by country of origin. The model utilizes ideas from the theory of discrimination in labour markets and from the theory of production. The model suggests that discrimination on the basis of nationality and costs associated with labour imports constitute the proximate determinants of the foreign workers mix. The theoretical predictions of the model could be tested empirically should data become available.
Keywords: Economics; Economics